Serum magnesium and its association with vascular calcification in chronic kidney disease patients on haemodialysis - B., Prasanna K.; K., Sharavanan T. V.; S., Ekanthalingam; I., Kannan (International Journal of Research in Medical Sciences, 2019)
Background: Cardiovascular disease is one of the leading causes of death in chronic kidney disease (CKD). It has been observed that haemodialysis patients have a high prevalence of cardiac risk factors with further risk due to abnormal mineral metabolism. A study has demonstrated that a higher serum magnesium significantly decreased the mortality risk in haemodialysis patients and lower serum Mg level has been found to be associated with increased mortality in them. The aim of the study was to characterize the relationship between Mg level and vascular calcification in CKD patients. Methods: It was a cross sectional study conducted in 100 CKD patients attending outpatient and inpatient ward of Tagore Medical College and Hospital, Chennai, Tamil Nadu, India. Serum magnesium levels will be measured using Xylidyl blue method. Carotid intimal medial thickness will be measured using Doppler. Results: In the study 10 patients did not show the sign of any calcification. Among the remaining 90 patients, 42 patients showed calcification and 48 patients showed stenosis. The statistical analysis showed a spearman correlation coefficient value of 0.201 thus showing only a weak association. Conclusion: The present study showed that only a weak relationship exists between the magnesium level and vascular calcification.